Criminal rehabilitation through medical intervention : moral liability and the right to bodily integrity - Douglas, T (Springer Netherlands, 2014)
Criminal offenders are sometimes required, by the institutions of criminal justice, to undergo medical interventions intended to promote rehabilitation. Ethical debate regarding this practice has largely proceeded on the assumption that medical interventions may only permissibly be administered to criminal offenders with their consent. In this article I challenge this assumption by suggesting that committing a crime might render one morally liable to certain forms of medical intervention. I then consider whether it is possible to respond persuasively to this challenge by invoking the right to bodily integrity. I argue that it is not.